Obesity and developmental functioning among children aged 2-4 years - John Cawley; Christa Katharina Spieß (Deutsches Institut für Wirtschaftsforschung (DIW), 2008)
In developed countries, obesity tends to be associated with worse labor market outcomes. One possible reason is that obesity leads to less human capital formation early in life. This paper investigates the association between obesity and the developmental functioning of children at younger ages (2-4 years) than ever previously examined. Data from the German Socio-Economic Panel Study are used to estimate models of developmental functioning in four critical areas (verbal skills, activities of daily living, motor skills, and social skills) as a function of various measures of weight (including BMI and obesity status) controlling for various child and family characteristics. The findings indicate that, among boys, obesity is a significant risk factor for lagged development in verbal skills, social skills, and activities of daily living. Among girls, weight generally does not have a statistically significant association with these developmental outcomes. Further investigations show that the correlations exist even for those preschool children who spend no time in day care, which implies that the correlation between obesity and developmental functioning cannot be due to discrimination by teachers, classmates, or even day care providers.
Keywords: I12; J24; 330; Obesity; human capital; children; child development; Germany; gender; Gesundheitsrisiko; Kinder; Bildungsniveau; Geschlecht; Deutschland